Effects of senescent lens epithelial cells on the severity of age-related cortical cataract in humans: A case–control study. Issue 25 (June 2016) - Fu, Qiuli; Qin, Zhenwei; Yu, Jiexin; Yu, Yinhui; Tang, Qiaomei; Lyu, Danni; Zhang, Lifang; Chen, Zhijian; Yao, Ke
Abstract : Abstract: The aging of lens progenitor cell has been repeatedly proposed to play a key role in age-related cataracts (ARCs), but the mechanism is far from being understood. The present study aims to investigate the relationship between aging of lens progenitor/epithelial cells and the 4 subtypes of ARCs in humans. Lens capsules, which were collected from ARC patients during surgery, were divided into 3 groups according to the age of patients (50–60, 60–80, and >80 years). The expressions of lens progenitor cell-related markers Sox2, Abcg2, and Ki67 were first examined in human lens epithelial cells (HLECs) in situ. Then, the percentage of senescent and SA-β-gal + HLECs isolated from lens capsules were quantified. Finally, the potential relationships between the percentage of senescent (and SA-β-gal + ) HLECs and the severity of ARCs were analyzed. Ki67 +, Sox2 +, and Abcg2 + HLECs in lens capsules were clearly more abundant in young people than in patients older than 50 years, and they were almost absent in patients older than 60 years. The percentage of primary HLECs with aging morphology increased with age, consistent with the results of SA-β-gal + primary HLECs. Only cortical cataract classification was found to be strongly related to the percentage of SA-β-gal + and senescent HLECs. Our study gave the initial evidence on the dynamical change of lens stem/progenitor cells in human lens capsule with age and suggested that lens progenitor/epithelial cell aging is important in the severity of cortical cataracts.